A roadmap in enhancing digital marketing capabilities at Saidiha multi products: University-community development participatory action research - Rosangeline, S.; Vithursiya, S.; Neojetha, T.; Niranchana, S.; Wimash, R.; Lasindu, T.G.R.M.; Jeethusha, S.; Kiritharan, S.; Dilogini, S. (Rajarata University of Sri Lanka, 2024)
This study investigates the adoption of digital marketing solutions by Micro, Small, and Medium Enterprises (MSMEs) in Sri Lanka, focusing specifically on Saidiha Multi Products in Nallur, Northern Province. The primary objectives are to identify the barriers MSMEs face in adopting digital marketing technologies and propose effective strategies for enhancing their digital marketing capabilities. The research reveals that Saidiha Multi Products, like many MSMEs in developing countries, encounter significant challenges, such as limited resources, financial constraints, and competition from larger enterprises. Additionally, the enterprise lacks adequate knowledge of digital marketing, compounded by a small workforce of just five employees. Using a qualitative approach, marketing specialization students from the University of Jaffna conducted participatory action research employing narrative inquiry to gather personal stories and insights from stakeholders. This method provides rich qualitative data on the transition from traditional marketing to digital platfonns. Tools, such as photovoice, allowed participants to document community strengths and challenges through photography, fostering insightful discussions. Focus group discussions facilitated collective insights and collaborative reflection, whereas participatory mapping visually depicted the spatial and social aspects of the business environment. The findings suggest that Saidiha Multi Products can enhance its online presence by leveraging tailored, cost-effective digital tools, and integrating traditional and online marketing channels. Recommended strategies through PAR include conducting awareness sessions for employees and owners on effective digital marketing techniques, implementing automated communications through email and SMS notifications, and developing a personalized website. Strengthening their social media presence and receiving ongoing consultation on emerging digital marketing techniques will further enhance their market expansion and customer engagement efforts.In conclusion, this research lays a solid foundation for enhancing digital marketing strategies among similar MSMEs in Sri Lanka. By addressing the identified barriers and implementing the proposed strategies, MSMEs can improve their sustainability and competitiveness in an increasingly digital market landscape.
Keywords: Digital marketing adoption; Digital transformation strategies; Marketing capability enhancement; MSMEs in Sri Lanka; Participatory action research